Loading

Loading

let y = lnx therefore e^y = x then differentiating both sides we get: dy/dx (e^y) = 1 dy/dx = 1/(e^y) and as e^y = x dy/dx = 1/x when y = lnx

One to one online tution can be a great way to brush up on your Maths knowledge.

Have a Free Meeting with one of our hand picked tutors from the UK’s top universities

Find a tutor

One to one online tution can be a great way to brush up on your Maths knowledge.

Have a Free Meeting with one of our hand picked tutors from the UK’s top universities

Find a tutor